Quantity of Germination Seed Response to Combustion Duration and Light Treatments in Jabon (Anthocephalus cadamba (Roxb.) Miq.) - Eliza Gusmira; Vauzia Vauzia (Bioscience, 2018)
This research was aims to determine the response of jabon seed germination  toward duration of combustion and light. This research was conducted from January to June 2018 at the Biology Laboratory and FMIPA UNP greenhouse. The design used was RAL with 2 factors. The first factor is the duration of combustion and the second factor is the light treatment. Based on the design obtained 10 treatment combinations and each treatment was repeated 3 times so that there are 30 units of experiment. Parameter observed is the number of seeds  germination. The results showed that light treatment, combustion duration treatment, and interaction between combustion duration and light give good effect on the number of seeds  germination. The seeds with the combustion treatment for 15 (A2) minutes had the highest number of sprouts that was 342.83 sprouts per 0.2 gram of jabon seeds. For light factor, many seeds germinate on the shelter treatment (B2) of 349.59 seeds per 0.2 gram of seed. While the combination of treatments showed that the best number of seeds germinated was in the combustion treatment 12.5 minutes with germination in the sheltered place (A1B2) that produced 564.67 sprouts per 0.2 gram of seed.